Inhibitory Effects of Phellodendri Cortex Against Airway Inflammation and Hyperresponsiveness in Ovalbumin-Induced Murine Asthma Model - Seong-Kyeom Kim; Ji-Won Do; Seong-Kyun Lee; Jae-Ho Park; Ju-Hyoung Kim; Heung-Bin Lim (Molecules)
Phellodendri cortex (PC), the dried trunk bark of Phellodendron amurense RUPR, has traditionally been used to treat patients who suffer from gastroenteritis, abdominal pain or diarrhea. Its major bioactive compounds include alkaloids and limonin, and many physiological activities including anti-microbial, anti-ulcer and anti-cancer as well as anti-inflammation have been reported. Although PC is an effective anti-inflammatory natural substance that inhibits the inflammatory response, its effect on allergic asthma has not yet been investigated. The aim of this study was to evaluate the anti-asthmatic effects of PC in an ovalbumin (OVA)-induced murine model of asthma. As a result, PC inhibited airway eosinophil accumulation, the influx of inflammatory cells, airway hyperresponsiveness (AHR), production of Th2 cytokines (IL-4, IL-5 and IL-13) and tumor necrosis factor-α (TNF-α) in the bronchoalveolar lavage fluid and/or lung, as well as OVA-specific immunoglobulin E (IgE) in the serum. Furthermore, PC suppressed the gene expression of IL-4, IL-5, IL-13, TARC and CCR3, and attenuated unique histological changes that are associated with airway inflammatory reactions including the infiltration of various inflammatory cells, collagen deposition and goblet cell hyperplasia in lung tissues. These results indicate that PC may have preventive and/or therapeutic effects for allergic asthma via the inhibition of cytokines, chemokines and chemokine receptors associated with allergic inflammation.